Supplemental cash loans to boost productivity in Nigeria - Ambler, Kate; Bloem, Jeffrey R.; Maruyama, Eduardo; Balana, Bedru; Olanrewaju, P.; Adewumi, B.; Essien, E.; Alabi, S.; Ogundare, M. (CGIAR System Organization, 2024)
Innovative combination of cash and input loans for smallholder farmers, improving their access to land, labor, and inputs to boost their productivity.